GNSS signal phase, TEC, and phase unwrapping errors. Issue 4 (10th October 2020) - Rino, Charles; Breitsch, Brian; Morton, Yu; Xu, Dongyang; Carrano, Charles
Abstract: Precise measurements of signal phase are essential for Global Navigation Satellite System (GNSS) position estimates. However, propagation through the earth's ionosphere imposes frequency‐dependent phase errors. The frequency dependence is exploited to correct phase errors proportional to total electron content (TEC) divided by frequency. Scintillation causes additional stochastic errors, which can become the largest phase error contribution. Both geometry‐free (GFCs) and ionosphere‐free (IFCs) frequency combinations are subject to such uncorrectable but generally small phase scintillation errors. A recent published study compared GPS TEC estimates derived from nominally identical L1‐L2 and L1‐L5 GFCs. The TEC errors establish an upper bound on uncorrelated single‐frequency scintillation error contributions. The measured TEC errors were verified with phase‐screen simulations. However, a known but largely overlooked phase unwrapping error affects the extraction of signal phase from phase‐screen complex signal realizations. This paper demonstrates a procedure for detecting and correcting phase‐unwrapping errors and discusses their ramifications.